Advanced Design Considerations for Permanent Magnetic Bearings: Bibliometric Insights and the Effects of Axial Displacement and Shaft Sagging on Horizontal Overhung Systems - Azman Jamaludin; M Zarhamdy Md Zain; Nur Safwati Mohd Nor (Bumi Publikasi Nusantara, 2026)
This study investigates the influence of axial displacement and shaft sagging on the performance of permanent magnetic bearings (PMBs) in horizontal overhung systems, supported by a bibliometric analysis of existing PMB research trends. The bibliometric review identifies dominant modelling approaches and reveals limited attention to axial displacement and shaft sagging effects in stacked PMB configurations. To address this gap, a modified analytical model based on Backers’s magnetic scalar potential method is developed by incorporating axial displacement and shaft sagging into the design framework. The proposed model is validated through experimental investigation using a horizontal overhung rotor system. The results show that the combined effects of axial displacement and shaft sagging significantly alter magnetic alignment and reduce effective wavelength, leading to performance degradation. Statistical equivalence testing confirms strong agreement between the proposed formulation and established analytical models. The findings provide improved design guidance for enhancing PMB stability, reliability, and efficiency in practical rotating machinery applications.